Estudio y análisis para la optimización del sistema de producción de viviendas de Hábitat para la Humanidad Costa Rica - Acosta-Jiménez, Catalina (Instituto Tecnológico de Costa Rica, 2006)
The following Professional Practice investigates the productive process of Habitat for Humanity Costa Rica. This non-profit organization is recognized for granting low income families with the opportunity to obtain appropriate housing by means of credits. The objective was to analyze the internal production process of houses for the company from the perspective of costs, duration, administration, as well as control and implementation. Likewise, the four constructive systems used by Habitat Costa Rica were studied; Prenac, Concrepal, Habicon and Integral Masonry System. During the investigation, deficiencies in the organization of the company through its process of production became evident. The results propose to improve the deficiencies of the system by means of a project plan integrating aspects of outreach, human control, planning, quality, resources, cost and delivery. This project will be of great benefit for the organization and the future families that become involved if the proposals are taken into account, since it will improve the ultimate operation and delivery system.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2006.
Keywords: Sistema; Proceso; Construcción; Administración; Planificación